Analisis Keterlibatan Orang Tua dalam Pengembangan Keterampilan Proses Anak Usia Dini di TK Generasi Amanah Desa Sampali Kecamatan Percut Sei Tuan Kabupaten Deli Serdang - Dwi Ningsih, Arie; Yus, Anita; Sudrajat, Ajat (Al Ittihadu, 2022)
This study aims to determine the involvement of parents in developing early childhood process skills. This study uses a qualitative method with a descriptive approach in the Generation Amanah Kindergarten. Sampling was based on purposive sampling with 8 parents as research subjects. Data collection techniques are questionnaires, interviews, observations, field notes and video recordings. Questionnaires, observation sheets and interview guidelines were used in data collection. The data were analyzed by reducing the data, presenting the data and concluding. The results showed that being together more than 12 hours a day, then accompanying children in learning, becoming discussion partners, providing learning facilities, and helping them solve problems, can develop children's process skills.